Maritime Trade and Religious Exchange in South and Southeast Asia: Buddhism, Merchants, and the Indian Ocean World - Dayalan Duraiswamy (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
From its inception, Buddhism has been intertwined with trade and traders, who significantly contributed to the patronage and dissemination of Buddhism across India and beyond. The ancient Buddhist monasteries in India appeared to offer spiritual guidance, lodging, and healthcare to long-distance traders, who reciprocated by donating to the monastic communities. Notably, many Buddhist centers in India are situated along ancient key trade routes. The literary sources and archaeological studies clearly highlight the crucial importance of the maritime interface in facilitating the exchange of Buddhist religious ideas, missionaries, and culture from India to different regions of the world. In fact, both local and foreign trade, along with traders, significantly contributed to the promotion of the Buddhist centres in India. Likewise, Indian traders and merchant guilds played an important role in supporting religious institutions overseas. The main objective of this paper is to comprehensively elucidate the relationship between Buddhism and trade, primarily drawing upon recent archaeological, epigraphical findings, and literary references. The paper also briefly addresses the diffusion of Islam into the Malay Archipelago through peaceful trade networks and the Sufi missions. The propagation of Islamic traditions along the coastal regions of Gujarat and Kerala in India, well before the establishment of the Islamic dynasty in North India, mainly occurred through the peaceful interaction of Arab merchants in this region via maritime trade.